Morphological and genetic identification of fungal genus/species in formalin‐fixed, paraffin‐embedded specimens obtained from patients with histologically proven fungal infection. Issue 8 (4th June 2021) - Sunagawa, Keishin; Nakamura, Shigeki; Sato, Yuko; Iida, Shun; Miyazaki, Yoshitsugu; Suzuki, Tadaki; Katano, Harutaka
Abstract: Background: Although fungi are found relatively easily by microscopic examination of pathological samples, identification of fungal genus and species in pathological samples is not easy because the morphological features of fungi are similar among genera and species. Objectives: A multiple real‐time PCR was developed for identification of fungal genus/species, and morphological characterizations of fungi were analysed in pathological samples. Patients/Methods: Seventy‐five formalin‐fixed paraffin‐embedded (FFPE) samples morphologically proven to contain any fungus were examined. A multiple real‐time PCR system was developed to identify 25 fungal genus/species in pathological samples. Morphology of fungus in the specimens was re‐reviewed retrospectively based on the results of real‐time PCR. Results: Real‐time PCR identified fungal genus/species in 56 of 75 (74.6%) specimens with histologically proven fungal infection. In 53 specimens of filamentous fungi, Aspergillus spp. (22 specimens), Cladosporium (8), Scedosporium apiospermum (4), Malassezia sympodialis (1) and Candida albicans (1) were identified. Pseudohyphae of Candida were confused with filamentous fungus in a case. Morphological observation suggested differences in the presence of septated or non‐septated hyphae, the filament size, and the branch angle among genus/species of filamentous fungi; however, genus/species was not able to be determined by their morphological features. In 22 specimens of yeasts, real‐time PCR allowed for the identification of Candida albicans (12 specimens), Candida glabrata (2), Cladosporium (2), Scedosporium apiospermum (2), Pichia kudriavzevii (1) and Aspergillus sydowii (1). Conclusions: These data suggest that it is difficult to identify fungal genus/species by morphological features alone. Real‐time PCR is useful to identify fungal genus/species in pathological samples.